1988
DOI: 10.1071/bi9880297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Myiasis and Acute Restraint Stress on Plasma Levels of Immunoreactive , ß-Endorphin, Adrenocorticotrophin (ACTH) and Cortisol in the Sheep

Abstract: Cutaneous myiasis in sheep arising from the activity of Lucilia cuprina larvae can result in significant physiological changes in susceptible animals. The stress imposed on the pituitary-adrenal axis of the sheep in response to myiasis and acute restraint is the subject of this investigation. Merino wethers were exposed to handling restraint, and blood sampling, during examination for blowfly strike; where necessary, they were treated for cutaneous myiasis. Significant changes in the plasma concentrations of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 8 publications
3
14
0
Order By: Relevance
“…This result is comparable to the findings in sheep in which there were the different responses of plasma β-EP and cortisol to a change of environment [25]. It was reported that in response to acute stress, plasma β-EP, ACTH and cortisol levels in sheep increased and then β-EP declined while ACTH and cortisol levels remained elevated [26]. The different profiles of β-EP and cortisol may be related to the half-life of plasma degradation of these two hormones.…”
Section: Discussionsupporting
confidence: 79%
“…This result is comparable to the findings in sheep in which there were the different responses of plasma β-EP and cortisol to a change of environment [25]. It was reported that in response to acute stress, plasma β-EP, ACTH and cortisol levels in sheep increased and then β-EP declined while ACTH and cortisol levels remained elevated [26]. The different profiles of β-EP and cortisol may be related to the half-life of plasma degradation of these two hormones.…”
Section: Discussionsupporting
confidence: 79%
“…Most information demonstrates that wool from flystruck areas has lower SS than wool from adjacent non struck areas (Butcher et al, 1984), although variation between samples was considerable. It is likely that stress plays a role in causing 'tender fleeces' of struck sheep, with high ACTH and cortisol levels found in sheep suffering from blowfly strike (Shutt et al, 1988) and other studies demonstrating administration of these hormones can cause a 'break in the fleece' (Lindner and Ferguson, 1956;Chapman and Bassett, 1970;Thwaites, 1972). For affected animals some wool is lost if the infected areas are shorn.…”
Section: Blowfly Strikementioning
confidence: 97%
“…For example, Shutt et al (1987) reported significant increases in serum cortisol in lambs following various surgical procedures. Other studies of sheep found increases in cortisol due to fly bites and handling by humans (Shutt et al, 1988) and after yarding and vehicular transport (Fell et al, 1985).…”
Section: Hormones Involved In This Reaction Include Adrenocorticotropmentioning
confidence: 99%